PENGARUH DIGITAL ADS TERHADAP PENJUALAN PRODUK PERJALANAN WISATA ROHANI KE TANAH SUCI OLEH VITRA TOUR - Aloysius Timoty; Rista Angriani; Khenny El Yabes Johananta (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study examines the influence of Digital Ads on the sales of religious tourism packages to the Holy Land by Vitra Tour. In the evolving digital era, digital marketing has become an essential component of business strategy, including in the religious tourism industry. Using a qualitative approach with in-depth interview methods, this research reveals that although Vitra Tour utilizes Digital Ads as one of its marketing strategies, word of mouth marketing remains the primary driver of sales growth. Research findings show that in the last three months, Vitra Tour served 31 participants with annual total participants reaching 80-100 people. Digital Ads play a role in increasing brand visibility and expanding market reach; however, the company's success is more determined by its ability to provide quality and meaningful travel experiences. This study concludes that an integrated marketing approach combining digital marketing with word of mouth marketing, coupled with a focus on service quality, is an effective strategy in building and maintaining business sustainability in the religious tourism sector.